The Use of G-form as an Assessment Instrument in Arabic Language Teaching Based on HOTS - Arifka Mahmudi (At-Tarbawi: Jurnal Kajian Kependidikan Islam, 2018)
Recently, Higher Order Thinking Skills is a new issues in Indonesia, because the government was inserted HOTS question into national exam in order to develop Indonesian education. One of the problem occuring that the students are not familiar to the question given, as the result, the student confuse and complait about it.. Thereby, the need to the assessment instrument that could help teacher and students to challenge it is the must. This study aimed to describe the use of G-form as a assessment instrument in arabic language teaching based on Higher Order Thinking Skills (HOTS), to ascertain availability of g-form features as an assessment instrument in arabic language teaching based on Higher Order Thinking Skills (HOTS), and to analyze the advantages and disadvantages of it. The research used a library research. The data was taken by interview the arabic teacher that use gmail as a test instrument in arabic language teaching based on HOTS, by reading books, national as well as international journals, and other references related to this discussion, and small experiment of g-form made. The result of this study claim that g-form can be used as an assessment instrument in Arabic language teaching based on Higher Order Thinking Skills (HOTS). The second are, although it has many advantages, in the other side, the disadvantages were found as well